ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN MANAJEMEN WAKTU PADA PROYEK KONSTRUKSI JALAN DI KOTA SAWAHLUNTO - Palusia, Abadi (Rang Teknik Journal, 2018)
Currently, many road projects are performing poorly for timely completion, an analysis of time road project implementation needs to be done on the contractor company, so that it can be known that the shortcomings and weaknesses done so far, which later can be an input for contractor, to be even better in the implementation of time management of a road construction project. In 2017 many packages of road construction works in Sawahlunto City. The purpose of this study is to determine the factors that affect the implementation of time management of road construction projects in Sawahlunto. The research method used is quantitative research method by spreading questionnaires to the respondents involved in road construction project in Sawahlunto City. Kata Kunci : Time Management, road, late